1990
DOI: 10.1111/j.1532-5415.1990.tb04418.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Nocturnal Fall in Blood Pressure in Elderly Persons with Alzheimer‐Type Dementia

Abstract: Circadian changes of the blood pressure and heart rate in elderly normotensive bedridden patients with severe dementia of the Alzheimer type (group D) were compared with those in elderly normotensive bedridden patients without dementia (group R), normotensive subjects with normal daily activity (group N), and hypertensive patients with normal daily activity (group H). In groups R, N, and H, the blood pressure increased in the afternoon and decreased at midnight; in group D, however, although it increased in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
0
22
1
Order By: Relevance
“…Otsuka et al [27] showed that nocturnal BP does not fall in elderly patients with Alzheimer's-type dementia. On the contrary, Kario and Shimada [28] presented an elderly hypertensive patient whose diurnal BP pattern changed after a minor ischemic stroke, suggesting that abnormal diurnal BP might originate from minor cerebrovascular ischemia.…”
Section: Brain Matter Volume and 24-h Blood Pressurementioning
confidence: 98%
“…Otsuka et al [27] showed that nocturnal BP does not fall in elderly patients with Alzheimer's-type dementia. On the contrary, Kario and Shimada [28] presented an elderly hypertensive patient whose diurnal BP pattern changed after a minor ischemic stroke, suggesting that abnormal diurnal BP might originate from minor cerebrovascular ischemia.…”
Section: Brain Matter Volume and 24-h Blood Pressurementioning
confidence: 98%
“…There is capillary microangiopathy especially in the cortex of patients with Alzheimer's disease [20]. The causes of this microangiopathy are probably similar as in other cases of microangiopathy [12]: Vascular risk factors such as old age, high blood pressure and type-II diabetes (including prediabetes/hyperinsulinemia) [2,5,6,17,18]. The fact that apolipoprotein E4 [3] and lack of estrogen in postmenopausal women are risk factors for Alzheimer's disease agree with this interpretation.…”
Section: Discussionmentioning
confidence: 51%
“…The reasons for this circadian susceptibility reside in the fact that AD affects the central nervous system, not only in the cognitive part, but also in the neuro-endocrine-vegetative sections, such as the hypothalamus and the suprachiasmatic nuclei (8,24-28), which notoriously regulate the circadian rhythmicity of many fundamental systems of human body (1-3). As far as the BP and HR circadian rhythm is concerned, the evidence existing in literature is in keeping with a possible loss of their circadian periodicity in most AD patients (15)(16)(17).…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, it has been found that AD is strongly disturbed in the day-night excursion of blood pressure (BP) because of the lack in nocturnal decrease (15)(16)(17), causing a condition called "non-dipping phenomenon" as well as cases defined "non-dippers. "…”
Section: Alzheimer's Disease (Ad) Is Said To Be Associated Withmentioning
confidence: 99%